A new compound heterozygous mutation in adult-onset Krabbe disease. (1st December 2020) - Meng, Xianghe; Li, Yingjiao; Lian, Yajun; Li, Yujuan; Du, Liyuan; Xie, Nanchang; Wang, Cui
Abstract: Purpose: Krabbe disease (KD) or globoid cell leukodystrophy is an autosomal recessive lysosomal disorder caused by a lack of the lysosomal enzyme galactocerebrosidase (GALC) because of mutations in GALC . Patients with KD exhibit a wide spectrum of clinical symptoms; therefore, their diagnosis can be challenging. We report the clinical features and gene mutations in a 48-year-oldpatient with adult-onset KD. Methods: We collected and analyzed clinical data of the patientwith a diagnosis of KD. Gene mutations were identified by whole exome sequencing. Results: We describe a case of adult-onset KD caused by a novel compound heterozygous mutation; a missense mutation, c. 1901 T > C (p. L634S); and a novel nonsense mutation, c.1005C > G (p. Y335X), in GALC . The disease onset started when the patient was 40 years old, and manifested as typical paralytic paraplegia. Magnetic resonance imaging indicated demyelination of the white matter, which is consistent with the typical symptoms of adult-onset KD. Biochemical analysis revealed GALC activity to be 1.5 nmol/17 h/mg protein, confirming its deficiency and KD diagnosis. Conclusions: Our findings provide evidence of a novel mutation, providing additional information toward to the GALC mutation database.